IMPLEMENTASI NILAI-NILAI SIBALIPARRI’ DALAM MANAJEMEN PEMBIAYAAN SEKOLAH - Asruddin, Asruddin (Eklektika: Jurnal Pemikiran dan Penelitian Administrasi Pendidikan, 2014)
The study aimed at discovering (i) the description of the implementation of sibaliparri’ values in funding school management, particularly the facility and infrastructure at SMAN 1 Campalagian, (ii) the supporting and inhibiting factors on the implementation of sibaliparri’ values at SMAN 1 Campalagian. This study was a qualitative research with a case study approach at the level of school’s organization. The study provided in-depth description on the implementation of sibaliparri’ values in funding school management at SMAN 1 Campalagian in Polewali Mandar district. The data sources of the study were determined purposively. Data were collected through interview and observation and validated by conducting triangulation and member check. The result of the study revelead that (i) the implementation of sibaliparri’ values in funding school management at SMAN 1 Campalagian was conducted well, which covered 3 functions of funding management: firstly, the school funding plan produced school development plan and school’s revenue and expanditure budget plan. Secondly, the finance implementation stage. Thirdly, the evaluation stage. Those three stage involving stakeholders, namely the principal, board of teachers, staff, committe, and society, (ii) the factors which influenced the implementation of sibaliparri’ values in funding school management were the internal factors such as enthuasiasm from the students in conducting the program by working together, brotherhood, and sincere; whereas, the weakness were lack of aids from the government in providing the facility and infrastructure. The external factors were the opportunity and challenges. The opportunity in this case was the value which instilled strongly to the people of Mandar in general.